L'informazione geografica mobile tra mercato consumer e professionale - Bernardini, Fulvio; Santarsiero, Domenico (GEOmedia, 2008)
Geographic Information changes and so does the media through which it is communicated. The geographical content producer as well as the converging force that followed it by means of technological evolutions in the positioning and mapping sectors, created the necessary basis to look forward with different eyes: the eyes of the prosumer. This article aims to clarify the situation highlighted in the context by providing a comparing between the evolution in the world of software and hardware.